Asymmetric exchange rate pass-through in an emerging market economy: the case of Mexico - Baharumshah, Ahmad Zubaidi; Fagir Omer, Abdalla Sirag; Siew, Voon Soon (Elsevier, 2017)
This paper applies a nonlinear Autoregressive Distribute Lag to examine the exchange rate pass-through into consumer price inflation in Mexico. Overall, the evidence confirmed that ignoring the asymmetric (sign) effect of exchange rate movements on inflation may lead to incorrect inferences and policy conclusions. Exchange rate fluctuation is transferred to prices level more during currency depreciation than appreciation. We compare the macroeconomic performances between pre- and post-inflation targeting, and our findings reaffirmed that the pass-through has weakened significantly after launching inflation targeting in 2001. This result implies that low inflation in the sample period examined is good for Mexico because exchange rate pass-through declines after 2001. Consumer prices have become less responsive to exchange rate movements. We further observe a revival (strengthening) of oil price pass-through to domestic inflation in the post- inflation targeting period.